Green chemistry water and its treatment - Benvenuto, Mark A. (Mark Anthony); Plaumann, Heinz; Al Amine, Hala; Al Amine, Hala; Bullerjahn, George S.; Bullerjahn, George S.; Darabi, Meisam; Darabi, Meisam; Dardona, Mohammed; Dardona, Mohammed; Dekker, Timothy; Dekker, Timothy; et al. (Green chemical processing ;, 2022)
The "greening" of industry processes, i.e. making them more sustainable, is a popular and often lucrative trend in Chemical Engineering. The 7th volume of Green Chemical Processing considers the role of water in sustainable chemistry and highlights innovations in the field of water treatment. The American Chemical Society's 12 Principles of Green Chemistry are woven throughout this text as well as the series to which this book belongs.